(untitled) - Winans, Kenneth G. (Novato, CA, 2007)
Amazingly, this is the first book , since the 1930's, devoted to traditional preferred stocks, Wall Street's best-kept secret in income investing. Although it's a mystery why this time-tested investment medium largely has been overlooked, the tips in this book will help readers navigate the world of preferred stocks and other income investments now and in the future. There is a single objective in mind ~ to make sure you're armed with useful information on how, why and when to take advantage of preferred stocks.
Keywords: Preferred stocks,Speculation